Laser management of hypertrophic burn scars: a comprehensive review. Issue 1 (16th January 2020) - Klifto, Kevin M; Asif, Mohammed; Hultman, C Scott
Abstract: Hypertrophic scars often develop following burn-related injuries. These scars can be cosmetically unappealing, but associated symptoms of pruritus, pain and restricted range of motion can impair a person's quality of life. Laser and light therapies offer a minimally invasive, low-risk approach to treatment, with a short postoperative recovery period. As laser technology developed, studies have shown decreased scar thickness, neuropathic pain and need for surgical excision, as well as improved scar pigmentation, erythema, pliability, texture, height and pruritus. In this review, we present the evolution of laser therapy for hypertrophic burn scars, how different types of lasers work, indications, perioperative considerations and guidelines for practice management.